Housing As We Grow Older: Design Considerations for a Supportive Environment: FCS3189/HE707, rev. 11/2002 - Peart, Virginia; Wilken, Carolyn (EDIS, 2003)
This document is Fact Sheet FCS 3189, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2002. First published: January 1994. Revised: November 2002. https://edis.ifas.ufl.edu/he707